An Enchancement Of Integrated Security System Unsing Data Flow Graph And Its Patterns - Dr.P.Kiran Kumar , G.Sirisha ,P. Deepika , A .Hima bindhu (International Journal of Advanced Science and Technology, 2020)
To pick up the information about programming security framework need assortment of perspectives, concerns and devices.